Detection of vessel wall calcifications in vertebral arteries using susceptibility weighted imaging - Adams, Lisa C.; Boeker, Sarah M.; Bender, Yvonne Y.; Fallenberg, Eva M.; Wagner, Moritz; Liebig, Thomas; Hamm, Bernd; Makowski, Marcus R. (Neuroradiology, 2017)
Purpose: Calcification of the brain supplying arteries has been linked to an increased risk for cerebrovascular disease. The purpose of this study was to test the potential of susceptibility weighted MR imaging (SWMR) for the detection of vertebral artery calcifications, based on CT as a reference standard. Methods: Four hundred seventy-four patients, who had received head CT and 1.5 T MR scans with SWMR, including the distal vertebral artery, between January 2014 and December 2016, were retrospectively evaluated and 389 patients were included. Sensitivity and specificity for the detection of focal calcifications and intra- and interobserver agreement were calculated for SWMR and standard MRI, using CT as a standard of reference. The diameter of vertebral artery calcifications was used to assess correlations between imaging modalities. Furthermore, the degree of vessel stenosis was determined in 30 patients, who had received an additional angiography. Results: On CT scans, 40 patients showed a total of 52 vertebral artery calcifications. While SWMR reached a sensitivity of 94% (95% CI 84–99%) and a specificity of 97% (95% CI 94–98%), standard MRI yielded a sensitivity of 33% (95% CI 20–46%), and a specificity of 93% (95% CI 90–96%). Linear regression analysis of size measurements confirmed a close correlation between SWMR and CT measurements (R2 = 0.74, p < 0.001). Compared to standard MRI (ICC = 0.52; CI 0.45–0.59), SWMR showed a higher interobserver agreement for calcification measurements (ICC = 0.84; CI 0.81–0.87). Conclusions: For detection of distal vertebral artery calcifications, SWMR demonstrates a performance comparable to CT and considerably higher than conventional MRI.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cerebrovascular risk; Stroke; Susceptibility weighted MRI; Vertebral artery calcification; Vertebral artery stenosis